Decision Making in Double-Pedicled DIEP and SIEA Abdominal Free Flap Breast Reconstructions: An Algorithmic Approach and Comprehensive Classification - Malata, Charles M.; Rabey, Nicholas G. (Frontiers in Surgery, 2015)
Introduction: The deep inferior epigastric artery perforator (DIEP) free flap is the gold standard for autologous breast reconstruction. However, using a single vascular pedicle may not yield sufficient tissue in patients with midline scars or insufficient lower abdominal pannus. Double-pedicled free flaps overcome this problem using different vascular arrangements to harvest the entire lower abdominal flap. The literature is, however, sparse regarding technique selection. We therefore reviewed our experience in order to formulate an algorithm and comprehensive classification for this purpose. Methods: All patients undergoing unilateral double-pedicled abdominal perforator free flap breast reconstruction (AFFBR) by a single surgeon (CMM) over 40 months were reviewed from a prospectively collected database. Results: Of the 112 consecutive breast free flaps performed, 25 (22%) utilised two vascular pedicles. The mean patient age was 45 years (range=27-54). All flaps but one (which used the thoracodorsal system) were anastomosed to the internal mammary vessels using the rib-preservation technique. The surgical duration was 656 minutes (range=468-690 mins). The median flap weight was 618g (range=432-1275g) and the mastectomy weight was 445g (range=220-896g). All flaps were successful and only three patients requested minor liposuction to reduce and reshape their reconstructed breasts. Conclusion: Bipedicled free abdominal perforator flaps, employed in a fifth of all our AFFBRs, are a reliable and safe option for unilateral breast reconstruction. They, however, necessitate clear indications to justify the additional technical complexity and surgical duration. Our algorithm and comprehensive classification facilitate technique selection for the anastomotic permutations and successful execution of these operations.